1970
DOI: 10.1159/000259621
|View full text |Cite
|
Sign up to set email alerts
|

Electron Probe and X-Ray Diffraction Microanalyses of Human Enamel Treated in vitro by Fluoride Solution

Abstract: Fluoride uptake, topographic distribution, and effect on human dental enamel following topical treatment (for 4 min, 8 min and 72 h) with an acidulated fluoride-phosphate solution have been studied by means of electron probe X-ray microanalysis and X-ray diffraction. The samples examined were divided into a non-washed group, and a washed group from which excessive and loosely bound F had been eliminated from the enamel. The topographic distribution of fluorine was demonstrated by electron probe X-ray microanal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 6 publications
3
28
0
Order By: Relevance
“…Fluoride may be incorporated in a soluble (CaF2) and/or permanently bound (fluoroapatite) form. In vitro studies have shown that fluoride applications deposit a reaction product coating of CaF2 on the anatomical surface of enamel 21,22) , and that fluoride is also permanently incorporated into the enamel during application [23][24][25] . It is highly probable that CaF2 creates mineral deposition in the porous zone of enamel and increases the microhardness 26) , thereby resulting in increased bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride may be incorporated in a soluble (CaF2) and/or permanently bound (fluoroapatite) form. In vitro studies have shown that fluoride applications deposit a reaction product coating of CaF2 on the anatomical surface of enamel 21,22) , and that fluoride is also permanently incorporated into the enamel during application [23][24][25] . It is highly probable that CaF2 creates mineral deposition in the porous zone of enamel and increases the microhardness 26) , thereby resulting in increased bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Peaks for β-TCP were also observed in the specimens laser-irradiated with 2.0 and 4.0 W. After laser irradiation with 4 W, all peak intensities decreased, indicating that the surface of the enamel melted partially and the structure changed, becoming amorphous-like, reducing its acid resistance. Because the XRD spectra for hydroxyapatite and fluorapatite are similar, it is difficult to identify the spectra obtained from Groups L and F. Previous studies reported that calcium fluoride formed on the enamel surface after fluoride application [31][32][33][34] . The relative atomic concentration of Group FL (11%) obtained from the XPS analysis was similar to that of fluorapatite, and the F 1s and Ca 2p spectra obtained for Groups L and FL were similar to those obtained for standard fluorapatite materials (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such access probably facilitates the delivery of buffering power and topical agents such as fluoride to the plaque-enamel interface. Saliva is not the only potential source of fluoride, however, the enamel surface is known to take up and to contain large amounts of fluoride [Weatherell et al, 1972] some of which is in a relatively unbound form and can diffuse out from the enamel [Baud and Bang, 1970]. This could be a source of fluoride for the plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have indicated that much of this may reside in the outer layers of the plaque associated with the salivary interface Kato et al, 1997]. It is possible that fluoride can be released from enamel surfaces after fluoride treatment [Baud and Bang, 1970]. What is unclear, however, is whether fluoride taken up by the underlying enamel could release fluoride into the deeper plaque adjacent to the enamel surface at risk.…”
mentioning
confidence: 99%